Poverty Alleviation Model on the Influence of Structural Poverty on Regional Development - Noni Komalasari; Sirojuzilam Hasyim; Suwardi Lubis; Rujiman (Kurdish Studies, 2024)
In order to overcome poverty, the government has carried out various programs. However, the poverty rate has not yet decreased significantly and has even increased in post- covid-19. Various factors influence poverty, including structural poverty. This research aims to analyze the influence of structural poverty and its overcoming on regional development in Medan Belawan District. The respondents in this study were heads of households in Medan Belawan District who had received several poverty reduction programs totaling 393 heads of families. The analytical tool used in this research is structural equation modeling. The research results show that (1) Structural poverty has a significant effect on poverty reduction; (2) Structural poverty has a significant influence on the development of the Medan Belawan District area; (3) Poverty reduction has a significant impact on the development of the Medan Belawan District area; and (4) Poverty alleviation mediates the influence of structural poverty on the development of the Medan Belawan District area.